Promoting workers' roles in the patientive employment movement based on Ho Chi Minh ideology - Nguyễn Thị Huyền Trang; Phạm Phương Lan (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
Ho Chi Minh's ideas on patriotic emulation are a unique component of Ho Chi Minh's philosophy system. The aforementioned ideals have awoken and encouraged our nation's priceless patriotic tradition of thousands of generations, producing exceptional spiritual power for all people to contribute to the country's progress. Workers have a significant place and duty among the subjects of the people, as the revolutionary leadership class and the pioneer in the patriotic emulation movement. The use of Ho Chi Minh's ideas to increase the role of workers in the contemporary patriotic emulation movement is critical.